2000
DOI: 10.1152/jn.2000.83.5.2682
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Disinhibition of Pyramidal Neurons by Activation of Nicotinic Receptors on Hippocampal Interneurons

Abstract: Nicotinic acetylcholine receptors (nAChRs) are expressed in the hippocampus, and their functional roles are beginning to be delineated. The effect of nAChR activation on the activity of both interneurons and pyramidal neurons in the CA1 region was studied in rat hippocampal slices. In CA1 stratum radiatum with muscarinic receptors inhibited, local pressure application of acetylcholine (ACh) elicited a nicotinic current in 82% of the neurons. The majority of the ACh-induced currents were sensitive to methyllyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(173 citation statements)
references
References 53 publications
9
162
2
Order By: Relevance
“…For example, two hippocampal pyramidal cells connected to the same GABAergic interneuron readily synchronize their firing after recovering from the inhibition evoked by the interneuron (25). Also, in the hippocampus, ACh-dependent activation of interneurons produces inhibition of pyramidal cells followed by rebound spiking (26), and endogenous cortical ACh recently has been shown to enhance synchronized interneuron activity via activation of ␣4␤2 nAChRs (27). Importantly, in human focal cortical dysplasia tissue in vitro ictal activity is initiated via a synchronization mechanism that requires sustained activation of GABA A receptors (28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, two hippocampal pyramidal cells connected to the same GABAergic interneuron readily synchronize their firing after recovering from the inhibition evoked by the interneuron (25). Also, in the hippocampus, ACh-dependent activation of interneurons produces inhibition of pyramidal cells followed by rebound spiking (26), and endogenous cortical ACh recently has been shown to enhance synchronized interneuron activity via activation of ␣4␤2 nAChRs (27). Importantly, in human focal cortical dysplasia tissue in vitro ictal activity is initiated via a synchronization mechanism that requires sustained activation of GABA A receptors (28).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that activation of α7 receptors could influence GABA release in the hippocampus. Physiological studies in rat hippocampal slices have confirmed the presence of α7 receptors on interneurons in all layers of area CA1 (Alkondon et al, 1998;Buhler and Dunwiddie, 2001;Frazier et al, 1998b;Frazier et al, 1998a;Jones and Yakel, 1997;McQuiston and Madison, 1999) as well as GABA-mediated inhibition of CA1 pyramidal cells following activation of α7 receptors on CA1 interneurons (Alkondon and Albuquerque, 2001;Buhler and Dunwiddie, 2002;Ji and Dani, 2000). It seems reasonable to hypothesize that α7 receptors may also modulate GABA release from interneurons in hippocampal area CA3 given that α-BTX binding has been observed on CA3 interneuron subtypes (Freedman et al, 1993) that are known to make synaptic contact with CA3 pyramidal cells (Freund and Buzsaki, 1996).…”
Section: Altered Gaba Releasementioning
confidence: 92%
“…In addition, nAChRs can modulate GABAergic transmission in multiple brain areas, such as thalamus, cortex, hippocampus, and interpeduncular nucleus (Lena et al, 1993;Alkondon et al, 1997Alkondon et al, , 2000Lena and Changeux, 1997;Fisher et al, 1998;Radcliffe et al, 1999). Modulation of GABA neurons by nAChRs has been most extensively studied in the hippocampus, where GABAergic interneurons express multiple nAChR subtypes (Alkondon et al, 1997;Jones and Yakel, 1997;Frazier et al, 1998b;McQuiston and Madison, 1999;Ji and Dani, 2000). The physiologic impact of nAChR activation is critically dependent upon their localization.…”
Section: Nicotinic Modulation Of Gabaergic Transmission In the Vtamentioning
confidence: 99%